Pengaruh Kompetensi kerja, Komunikasi Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT Capital Megah Mandiri Medan - Venice Venice; Cut Fitri Rostina; Marcello Sachio (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2020)
The decline in employee performance is influenced by many factors. At PT Capital Megah Mandiri, it is seen that there is a decline in employee performance as indicated by the company's unachieved realization of targets. This study aims to see the factors that affect the decline in employee performance at PT. Capital Megah Mandiri, the competence, satisfaction and employee communication factors. The approach and type of this research is descriptive quantitative with the target population of the study are all employees of PT. Capital Megah Mandiri. The data analysis technique used multiple linear regression. The results of the analysis prove that competence, communication and satisfaction have a significant effect on employee performance. It is known that competence is the most significant factor and has the greatest impact on the decline in employee performance of PT. Capital Megah Mandiri